Comparing Scoring Systems used in Intensive Care Unit Regarding Predictive Roles Mortality - Şule Özbilgin; Kubilay Demirağ; Asuman Sargın; Mehmet Uyar; Ali Reşat Moral (Galenos Yayinevi, 2011)
Objective: It is important to use scoring systems for admission to ICU or transfer of patients from ICU to other clinics. In our study we compared performance of APACHE II, SAPS II, MPM0 II and LODS scoring systems to predict mortality rates. Materials and Methods: All patients admitted to anesthesiology and reanimation clinic between 2005-2006 were evaluated retrospectively. The study included 615 patients. Demografic data were collected and APACHE II, SAPS II, MPM0 II, LODS scores calculated. ICU and hospital stay, clinic where the patient was referred from and 6-month mortality were noted. Results: APACHE II, SAPS II, MPM0 II and LODS all found to be significantly associated with mortality prediction in ICU. In ROC analysis area under curve was calculated as 0.812 (95% CI: 0.778-0.845) for APACHE II; 0.841 (95% CI: 0.810-0.872) for SAPSII; 0.797 (95% CI: 0.763-0.832) for MPM0 II; and 0.815 (95% CI: 0.781-0.849) for LODS. ICU mortality was 46%. Scoring systems were not associated with ICU stay when evaluated with Pearson correlation. All the values in ROC systems showing the relationship between scoring systems and 6-month mortality were under 0.5 and these values were not significant. 6-month ICU mortality was 24%. Conclusion: Out of 615 ICU patients, 289 were deceased and 326 were discharged. Although APACHE II, SAPS II, MPM0 II and LODS all were significantly associated with ICU mortality prediction, when compared with the other two scoring systems SAPS II ve LODS seems to be more suitable for ICU mortality prediction due to more feasibility, higher specifity and sensitivity. (Journal of the Turkish Society of Intensive Care 2011; 9: 8-13)